Surgical Treatment of Intestinal Endometriosis: Outcomes of Three Different Techniques - Fernando Bray-Beraldo; Ana Maria Gomes Pereira; Cláudia Gazzo; Marcelo Protásio Santos; Reginaldo Guedes Coelho Lopes (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To outline the demographic and clinical characteristics of patients with deep intestinal endometriosis submitted to surgical treatment at a tertiary referral center with a multidisciplinary team, and correlate those characteristics with the surgical procedures performed and operative complications. Methods A prospective cohort from February 2012 to November 2016 of 32 women with deep intestinal endometriosis operations. The variables analyzed were: age; obesity; preoperative symptoms (dysmenorrhea, dyspareunia, acyclic pain, dyschezia, infertility, urinary symptoms, constipation and intestinal bleeding); previous surgery for endometriosis; Enzian classification; size of the intestinal lesion; and surgical complications. Results Themean age was 37.75 (±5.72) years. A total of 7 patients (22%) had a prior history of endometriosis. The mean of the largest diameter of the intestinal lesions identified intraoperatively was of 28.12 mm (±14.29 mm). In the Enzian classification, there was a predominance of lesions of the rectum and sigmoid, comprising 30 cases (94%). There were no statistically significant associations between the predictor variables and the outcome complications, even after the multiple logistic regression analysis. Regarding the size of the lesion, there was also no significant correlation with the outcome complications (p = 0.18; 95% confidence interval [95%CI]:0.94-1.44); however, there was a positive association between grade 3 of the Enzia classification and the more extensive surgical techniques: segmental intestinal resection and rectosigmoidectomy, with a prevalence risk of 4.4 (p < 0.001; 95%CI:1.60-12.09). Conclusion The studied sample consisted of highly symptomatic women. A high prevalence of deep infiltrative endometriosis lesions was found located in the rectum and sigmoid region, and their size correlated directly with the extent of the surgical resection performed.